Draft Fifth Five Year Plan of Andaman and Nicobar Islands (1974-79) (Volume V) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1974)
State income estimates provide a most comprehensive single indicator of the overall performance of a State's economy and furnish a very useful insight into the structural relationship obtaining among different sectors of the economy. These estimates serve as a very important tool both for the formulation of plans as well as for the measurement of economic growth achieved as a result of implementation of development plans.
Andaman and Nicobar Administration